2021
DOI: 10.3389/fmed.2021.782624
|View full text |Cite
|
Sign up to set email alerts
|

Social Isolation Is Associated With Rapid Kidney Function Decline and the Development of Chronic Kidney Diseases in Middle-Aged and Elderly Adults: Findings From the China Health and Retirement Longitudinal Study (CHARLS)

Abstract: Background: There is limited evidence on the relationship between social isolation and renal outcomes. To address this gap, this study estimated the prospective relationship of social isolation with rapid kidney function decline and the development of chronic kidney disease (CKD) in middle-aged and elderly Chinese with normal kidney function.Methods: We analyzed data from 3,031 participants aged ≥ 45 years with baseline estimated glomerular filtration rates (eGFR) ≥ 60 ml/min/1.73 m2. All data were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Predialysis patients usually have significant muscle atrophy, which is the main factor for weakness [ 14 ]. Similarly, older patients on hemodialysis are gradually isolated from their social environment due to comorbid diseases, deaths of family members, physical weakness, and hearing loss [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predialysis patients usually have significant muscle atrophy, which is the main factor for weakness [ 14 ]. Similarly, older patients on hemodialysis are gradually isolated from their social environment due to comorbid diseases, deaths of family members, physical weakness, and hearing loss [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also found that pensioners had statistically high levels of depression. This can be attributed to the fact that retirement usually leads to social isolation in older adults, which is a significant factor in depression [ 15 ]. Additionally, retirement has a close relationship with decreased working ability in these patients, since working-age individuals on hemodialysis have difficulties in maintaining employment due to co-morbid diseases, increased fatigue, frequent hospitalizations, and the long duration of hemodialysis sessions, each lasting four hours, three times a week [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was a rapid decrease in eGFR, as defined by a reduction of > 5 mL·min –1 ·(1.73 m 2 ) –1 /year [ 22 , 23 ]. A reduction in eGFR of > 15 mL/min·(1.73 m 2 ) after three years was considered to indicate the progression of kidney function.…”
Section: Methodsmentioning
confidence: 99%
“…94 In a study including 3031 individuals with baseline estimated glomerular filtration rates (eGFR) ≥ 60 mL/min/1.73 m 2 , Zhou et al showed an independent association between social isolation and the risk of rapid fall in the eGFR as well as CKD onset. 94 In another study, Moorthi et al showed that individuals with CKD stage 3b-5 had significantly decreased social contact and social participation and mobility limitation was an important risk factor for these conditions. 95 A recent review also discusses the impact of loneliness in the development of anorexia in older patients with endstage renal disease.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%